UV Spectrophotometric Method for the Estimation of Valacyclovir HCl in Tablet Dosage Form - M. Ganesh; C. V. Narasimharao; A. Saravana Kumar; K. Kamalakannan; M. Vinoba; H. S. Mahajan; T. Sivakumar (E-Journal of Chemistry)
A simple, sensitive, highly accurate UV spectrophotometric method has been developed for the determination of valacyclovir in bulk and tablet dosage form. Solution of valacyclovir in 0.1N HCl shows maximum absorbance at 255 nm. Beer’s law was obeyed in the concentration range of 5-25 mcg mL-1 with 1.0910x104 mol-1 cm-1, the slope, intercept, correlation coefficient, detection and quantitation limits were also calculated. The proposed method has been applied successfully for the analysis of the drug in pure and in its tablets dosage forms. Result of percentage recovery and placebo interference shows that the method was not affected by the presence of common excipients. The percentages assay of valacyclovir HCl in tablet was 99.82%. The method was validated by determining its sensitivity, accuracy and precision which proves suitability of the developed method for the routine estimation of valacyclovir in bulk and solid dosage form.